Preliminary Report of Encephalitis Surveillance Study in Rajshahi Medical College Hospital - Hussain, Sultana M; Hossain, MJ; Ekram, ARMS; Gurley, ES; Alam, MM; Montgomery, SP; Azad, MAK; Breiman, RF; Luby, SP; Ahmed, I; Rahman, MF; Siddiqui, AB (TAJ: Journal of Teachers Association, 2009)
More than 100 different viruses, bacteria, toxins and drugs can cause acute encephalitis. A prospective, hospital-based study to define the causes of encephalitis in Bangladesh began in June 2003. At Rajshahi Medical College Hospital in one year 105 out of 391 suspected encephalitis patients were enrolled. The specimens were collected from these patients and were tested for a variety of pathogens at twelve laboratories at the Centers for Disease Control and Prevention (CDC) in Atlanta and Ft. Collins, USA. Among the first 105 patients enrolled, the median age of the patient was 18 years; 55% were male. Twenty-four percent (n-25) died in hospital or before completing the follow-up. Thirteen out of 105 (12.38%) patients had Japanese encephalitis; three of the encephalitis patients had a positive test result of having recent infection with dengue virus and one had encephalitis due to alpha virus, another patient had encephalitis due to echovirus. Three (2.8%) were polymerase chain reaction (PCR) or culture positive for Streptococcus pneumoniae, and 4 for Mycoplasma pneumoniae. No Nipah virus infection was identified among the first 105 serum samples tested. These data suggest that Japanese encephalitis virus is an emerging cause of encephalitis in northern part of Bangladesh. doi: 10.3329/taj.v17i2.3449 TAJ 2004; 17(2): 75-79